Review of the Possible Relationship and Hypothetical Links Between Attention Deficit Hyperactivity Disorder (ADHD) and the Simple Sleep Related Movement Disorders, Parasomnias, Hypersomnias, and Circadian Rhythm Disorders - Walters, Arthur S. (American Academy of Sleep Medicine, 2008)
Recent evidence has been accumulating that the sleep of individuals with attention deficit hyperactivity disorder (ADHD) is not only disrupt- ed in a nonspecific way but that ADHD has an increased association with simple sleep related movement disorders such as restless legs syndrome/periodic limb movements in sleep (RLS/PLMS), rhythmic movement disorder (body rocking and head banging), and parasom- nias, such as disorders of partial arousal (sleep walking, sleep ter- rors, and confusional arousals). In addition increased associations have been reported between ADHD and hypersomnias such as nar- colepsy and sleep apnea as well as circadian rhythm disorders, such as delayed sleep phase syndrome. These relationships are reviewed and the implications for such associations are explored. Patients with sleep disorders should be queried about the symptoms of ADHD and vice versa. CITATION: Walters AS; Silvestri R; Zucconi M; Chandrashekariah R; Konofal E. Review of the Possible Relationship and Hypothetical Links Between Attention Deficit Hyperactivity Disorder (ADHD) and the Sim- ple Sleep Related Movement Disorders, Parasomnias, Hypersomnias, and Circadian Rhythm Disorders. J Clin Sleep Med 2008;4(6):591-600.